Diskresi Hakim Dalam Memutuskan Perkara Dispensasi Kawin di Pengadilan Agama Sukadana - A. Jamil; Cut Aja Sela Nirmala; Inge Maulidina Putri (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
Discretion means independence and authority. Independence from the essence of discretion is independence and freedom to take appropriate actions. At the same time, authority is the power of decision in determining the applicable law. The nature of this discretion is following the position and authority of the judge as the executor of legal power. As expressly stated in the Constitution, judges are independent judiciary administrators and this is following Article 24 of the 1945 Constitution which refers to Article 21 of RI Law No. 4 of 2004 and its relation to legal freedom in marriage. and regarding the relationship with the marriage dispensation case, the judge based on the evidence will confirm the facts, namely that there is a valid reason according to law for the dispensation and after there is a reason, the judge will consider the law. The research used by researchers in this study is empirical or sociological legal research. Empirical or sociological research or field research. The nature of this research is descriptive. Descriptive research. Prescriptive research is research that aims to provide an overview or formulate a problem based on existing conditions or facts. The results of the study show that judges do not only base their decisions on laws and regulations but also use their power and freedom to make fair decisions based on their conscience. The judge granted many divorce requests submitted to the Sukadana Religious Court. This is because the judge prioritizes the concept of maslahah. The wisdom of the judges of the Sukadana Religious Court in accepting applications for marriage certificates is included in the category of "Hifd al-Nasl" (safeguarding offspring) in the Maqashid Syariah theory. This effort is seen as a way to prevent the applicant's child from committing adultery.